PEMBENTUKAN KARAKTER ANAK USIA DINI MELALUI FILM ANIMASI IPIN DAN UPIN - Dahniar Dahniar (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
The golden age (range 0 to 6 year old) is very important for a child, the formation of character in this age range greatly determines the next stage of the chid’s character development. This age is when children are still learning, interested in many things without knowing right or wrong. Television is one of the interesting activities for early childhood where they are interested in imitating what they watch, so that gradually it will affect their character. Many animated films are shown on television, on of which is Ipin Upin animation which is classified as islamic animation. However, this is where the parents job is to accompany, direct or help children understand the meaning contained in each scene so that children can understand which ones can be imitated and which cannot. This study used descriptive qualitative method. Data collection was taken though interviews, non partisipant observation and literature study. The result obtained are that more or less Ipin dan Upin animated films have a positive or negative influence on the formation of early childhood character.